Framing Analysis of Iran-Israel’s 2024 Conflict in Kompas.id, Aljazeera.com, and NYTimes.com - Nuraini, Fira Pujia; Mulyana, Deddy; Herawati, Maimon (Jurnal Kajian Jurnalisme, 2024)
This research seeks to explore how the Israel-Iran conflict in April 2024 is framed by the online media Kompas.id, Aljazeera.com, and NYTimes.com. This research aims to investigate how different narratives about the long-standing conflict pertaining to Iran-Israel complex tensions are carried by these media that present distinct geopolitical perspectives. This study uses a qualitative approach employing Robert M. Entman's framing model analysis consisting of four elements: defining the problem, diagnosing causes, making moral judgments, and suggesting solutions. Data was captured from articles written during a specific period in April 2024. Examination may include determining bias, thematic emphases and narrative strategies for each story. It was found that each media outlet had different frames for conflict. Kompas.id tends to take a more neutral approach. Aljazeera.com emphasizes the implications of Middle Eastern geopolitics of the conflict, while NYTmes.com concentrates on the broader international impact as well as the foreign policy interests of America. Such variations are politically and culturally biased according to the diverse media outlets used. This research highlights the biases and priorities reflected in the media report of the geopolitics conflict presented by various media outlets and provides insight into how the conflict is portrayed by the large media.